A CLINICAL STUDY TO DETERMINE THE ROLE OF GUDA HARITAKI AND PUNARNAVA MANDURA IN THE MANAGEMENT OF PANDU ROGA W.S.R. TO IRON DEFICIENCY ANAEMIA AMONG CHILDREN (International Journal of Ayurveda and Pharma Research, 2019)
Nutritional anaemia is frequently observed in India. Prevalence of anaemia in Indian children is 59% (Hb